An investigation of antimicrobial compounds for dental health care from the leaf and stem extracts of carissa bispinosa (L.) desf ex brenan (apocynaceae) - Shekwa, Wanda (My University, 2022)
Dental diseases are among the most prevalent diseases worldwide. A recent epidemiological survey has shown that about 49 to 83% people are affected by dental caries. Carissa bispinosa (L.) Desf. ex Brenan is one of the medicinal plants used traditionally to treat dental diseases. This study aims to investigate the effectiveness of antimicrobial compounds from the leaf and stem extracts of C. bispinosa on oral pathogens. Nine solvents (n-hexane, chloroform, dichloromethane, ethyl acetate, acetone, ethanol, methanol, butanol and water) were used for the extraction of the leaf and stem powder of C. bispinosa. Biochemical tests were performed to determine the presence of phytochemical constituents and the phytochemical profile was generated through thin layer chromatography (TLC). TLC- 2, 2-diphenyl-1-picrylhydrazyl (TLC-DPPH) assay was used to determine the qualitative antioxidant activity while DPPH free radical scavenging and ferric reducing power assay were used for the quantification of antioxidant activity. The antimicrobial activity was tested on five pathogens (Staphylococcus aureus, Enterococcus faecalis, Streptococcus pyogenes, Candida albicans and Candida glabrata) qualitatively using the TLC-bioautography assay and quantitatively using the minimum inhibitory concentration (MIC) assay. Cytotoxicity was tested on the THP-1 cell line using 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay. The active compound was isolated through open column chromatography and preparative-TLC guided by bioassays. Structural elucidation was achieved from the analysis of spectral data generated by nuclear magnetic resonance (NMR) techniques. A variety of phytochemicals were detected on the leaf and stem extracts. The extracts had high antioxidant activity, especially those extracted with polar solvents. All the pathogens, except C. glabrata, demonstrated susceptibility to the extracts on the qualitative assay. For the leaf extracts, methanol extract had the lowest average MIC value (0.81 mg/ml) making it the most activity across the microorganisms, whereas hexane had the highest MIC value (1.63 mg/ml). C. albicans demonstrated higher susceptibility with an average of 0.73 mg/ml while C. glabrata displayed the least (2.8 mg/ml). Compared to the leaf extracts, lesser activity was observed for the stem extracts on bioautography and MIC. The percentage viability was decreasing as the concentration of the extract was increasing. However, the highest concentration resulted xxiv in more than 50% cell viability. The compound was isolated as a white powder (10.5 mg). It was identified based on its physical properties, spectroscopic data and comparing the data with scientific literature and was found to be β-Sitosterol, a member of plant steroids (Phytosterols). The study is the first to detect the presence of the antimicrobial compound (β-Sitosterol) and isolate it from the leaves of Carissa bispinosa.
Thesis (M. Sc. (Microbiology)) -- University of Limpopo, 2022
Keywords: Dental diseases; Medicinal plants; Desf. ex Brenan; Antimicrobial compounds; Dental diseases; Dental public health; Dental pulp -- diseases; Medicinal plants